Reasons for pregnancy among women on prevention of mother-to-child transmission (PMTCT)program in Serowe-Botswana - Kanyinda, Muya (University of Limpopo (Medunsa Campus), 2010)
Thesis (MPH)--University of Limpopo,2009. === Background: Women living with HIV frequently report in the clinic with pregnancy despite their health status and knowledge of mother-to-child transmission HIV. This study assessed the level of knowledge of Prevention of Mother-to-Child Transmission (PMTCT) and the reasons for pregnancy among women on PMTCT in Serowe, Botswana. Objectives: The objectives of this study were to assess the level of knowledge of the PMTCT program and vertical transmission among HIV-positive women in Serowe; evaluate the reasons for pregnancy among HIV-positive pregnant women enrolled in the PMTCT program as well as describe the practices of family planning among these women in Serowe. Methodology: The study was a cross-sectional descriptive survey using qualitative method. Twenty six (26) participants attending PMTCT clinics at Serowe clinic, Nutrition clinic, and Kadimo clinic participated in the study between October and December 2008 after consenting to participate. Research assistants conducted in-depth interviews to collect socio-demographic data of the participants. Qualitative methods were used to collect data about the women’s level of understanding of the PMTCT program, reasons for falling pregnant, types and duration of their relationships with their partners and family planning practices. The interviews were conducted in the local language (Setswana) and then translated into English by the research assistant for transcribing. Their responses were audio taped. Results: The results indicated that most of pregnancies were unplanned. However, 26.9 % of participants said that they became pregnant because they desire to have another child. A number of participants ( 15.4%) indicated that they became pregnant because their partners wanted a child. Although all 26 participants had good knowledge and understanding of the family planning practices, but only 18 (69.2 %) had used the family planning methods before falling pregnant. The findings in this study revealed good social suport from the family members and the disclosure of HIV status was not a big issue to the participants. Majority of respondents (66.6%)) had good knowledge and understanding of the PMTCT program. One-third of the participants were single, ninety- six percentages of participants were unemployed, and about one-third of them live on less than 50 U$ dollars per month. Conclusion: As the desire to have children is usually perceived as a normal part of life for all women, including women living with HIV. Most women chose not to become pregnant after knowing their HIV status (HIV-positive) but the found themselves with unplanned pregnacy. The women with a procreative inclination were found to be more likely to choose to become pregnant which outweighed social support and personal health concerns. Additional factors included fear of transmitting HIV to their child, personal health-related concerns, unemploment and poverty. Participants had good knowledge of PMTCT program. The use of family planning by participants was poor despiste their good knowledge about it